A M(r) 95,000 polypeptide in Porphyridium cruentum phycobilisomes and thylakoids: Possible function in linkage of phycobilisomes to thylakoids and in energy transfer - Redlinger, Thomas (1982)
Two pigmented polypeptides with the same molecular weight (M(r) 95,000) were isolated from the photosynthetic apparatus of Porphyridium cruentum by sodium dodecyl sulfate/polyacrylamide gel electrophoresis. A blue polypeptide from phycobilisomes had absorption and fluorescence emission spectra similar to those of allophycocyanin. A green-pigmented polypeptide from photosynthetic membranes (free of phycobilisomes) contained chlorophyll a. Several properties were common to the M(r) 95,000 polypeptides from both sources: (i) identical molecular weights, (ii) identical gel electrophoresis patterns after limited protease digestion, and (iii) immunological crossreactivity with an IgG fraction directed against the M(r) 95,000 polypeptide from phycobilisomes. On the basis of this evidence, a common polypeptide exists in phycobilisomes and thylakoids, and it probably anchors the phycobilisome to the thylakoid membrane. The fluorescence emission overlap of the blue and green polypeptides suggests that they are involved in the transfer of energy from phycobilisomes to thylakoids.